Monginaia, a new genus of endemic bivalve from the lower Barremian of Teruel, eastern Spain, and the distribution of unionid bivalves in Spanish Cretaceous. (October 2022) - Delvene, Graciela; Munt, Martin C.; Royo-Torres, Rafael; Cobos, Alberto
Abstract: The present study focuses on a new record of freshwater bivalves from the lower Barremian Camarillas Formation of the Lower Cretaceous of Teruel, eastern Spain. A new genus Monginaia is described and included in a new family Monginaiidae (Unionida). This taxon is compared and contrasted with other European, Asiatic and North American species. This discovery provides new palaeogeographic data on the distribution and origin of the Unionida in Europe. Moreover, this taxon is an effective tool for the environmental reconstruction of the Spanish Cretaceous ecosystem where it coexisted with dinosaurs and crocodiles and other vertebrates.